Mammalian Atg9 contributes to the post‐Golgi transport of lysosomal hydrolases by interacting with adaptor protein‐1. Issue 24 (29th November 2017) - Jia, Shu; Wang, Yusha; You, Zhiyuan; Liu, Bo; Gao, Jinfeng; Liu, Wei
Abstract : Accumulating evidence has indicated a role for autophagy‐related (Atgs) proteins in cell regulation which is independent of their autophagic activities. As the only known transmembrane protein essential for autophagy, Atg9 cycles between the trans‐Golgi network (TGN) and endosomes. Here, we report a function for mammalian Atg9 (mAtg9) in the transport of lysosomal hydrolases which impacts the lysosomal degradation capacity. Depletion of mAtg9 inhibits the degradation of epidermal growth factor receptor and the maturation of cathepsin D and cathepsin L. mAtg9 interacts with adaptor protein‐1 (AP1) and the cation‐independent mannose‐6‐phosphate receptor, facilitating AP1 polymerization and the transport of cathepsin D from the TGN. These results suggest that mAtg9 may serve as a coreceptor of lysosomal hydrolases for their TGN export by cycling between the TGN and endosomes. Abstract :